(untitled) (Acta Scientiarum. Technology, 2025)
Hunger and malnutrition have been an important challenge facing the world, with food insecurity being their main contributing factor. However, as the solving strategies focus on increasing production, food losses that reduce availability for consumption and affect climate change tend to happen. In this study, the nutritional composition and microbiological quality of food losses in the central market of Merida, Mexico, were determined. The study population was composed of a set of discarded foods that were deposited in containers at the central market. Three types of sampling were obtained: for solid waste, for the calculation of the food percentage contained in the solid waste, and for chemical and microbiological analysis. The sample data was recorded and analyzed with descriptive statistics. The average solid waste generated per day was 1185.02 kg, with more than three-quarters (86.08%) of its content consisting of fruit and vegetable groups. No animal-derived foods were found among the food losses since this central market doesn’t supply them. The greatest amount of protein and fiber was present in vegetables, while fruits had the greatest amount of moisture and carbohydrates. The presence of microorganisms, mainly yeasts, was higher than the established limit, making the food unsuitable for human consumption. However, it was found to be a good source of lipids and organic matter, making them useful for composting, biofuel production, or the extraction of bioactive compounds.